Leaf Morphological Traits of then Shrub Species at the Tamaulipan Thorn Scrub - Balboa, Perla Cecilia Rodriguez; Rodriguez, Humberto Gonzalez; Silva, Israel Cantu; Parra, Artemio Carrillo; Lozano, Roque G. Ramirez (International Journal of Bio-resource and Stress Management, 2023)
The aim of this work was to conduct a research study of the leaf morphological traits of ten woody species that grow and develop in the Tamaulipan Thorn scrub Shrub land. Study species were Cordia boissieri, Helietta parvifolia (A.DC.), Condalia hookeri (M.C. Johnst.), Diospyros texana (Sheele), Diospyros palmeri (Eastw.), Zanthoxylum fagara (L. Sarg.), Sideroxylon celastrinum (Kunth T.D. Penn), Karwinskia humboldtiana (Schult. Zucc.), Celtis pallid (Torr.) and Celtis laevigata (Willd). Leaf morphological characteristics were leaf fresh weight (g), leaf area (cm2), leaf length (cm), leaf width (cm), petiole length (cm), total leaf length (cm), leaf dry weight (g), leaf water content (g) and specific leaf area (cm2 g-1).The results showed that the species Cordia boissieri got the highest value in all studied variables which ranged from 0.4167 g (leaf water content) to 101.4605 cm2 g-1 (specific leaf area). In contrast, the species Diospyros texana registered the lowest value in seven variables which ranged from 0.0217 (leaf water content) to 3.186 cm (Leaf total length. Correlation analysis showed highly significant relationships, both positive and negative, among studied leaf traits.